Save university arts from the bean counters - Petsko, Gregory (Nature (London), 2010)
Cutacks in non-science subjects by US colleges and universities are criticized. The arts and humanities have much to offer higher education, and the bean counters who want to slash them must be stopped before higher education is itself destroyed.